ANALYSIS OF INDONESIAN BOTTOM LANGUAGE REQUIREMENTS THAT RESULT FROM THE STORIES IN ALQURAN WITH CONTENT AND LANGUAGE INTEGRATED LEARNING APPROACH - Izzah Izzah; Zainal Rafli (Program Pascasarjana Universitas Negeri Jakarta, 2017)
The problem in this research is the incompatibility of teaching materials used with the needs of students and teachers of Indonesian class VII. Teaching materials should contain four language competencies, namely listening, speaking, reading, and writing in an integrative manner. In addition, Indonesian language learning should integrate with literature, culture, and religion. Thus, the demands of the 2013 curriculum that synergize between the core competencies 1 (KI 1) in the form of spiritual competence, Core Competence 2 (KI 2) in the form of social competence, Core 3 Competence (KI 3) in the form of knowledge competence, and Core Competence 4 (KI 4) in the form of skill competence can be done. For that, one solution is to display the story in the Qur'an as a raw material for learning Indonesian. Not just learners, parents also like the story. This paper offers how the story in the Qur'an can be the source text in Indonesian Language learning. In addition, the discussion in this paper also links various subjects. All of that is put together under one theme. Through the story in the Qur'an with CLIL approach Indonesian learning will be more interesting, actual, and dynamic because the story in the Qur'an is a true story that at the same time can teach the noble character. Keyword:Teaching Materials, history in Al quran, CLIL Approach